Changes of Langerhans cells during skin ageing - Zegarska, Barbara; Pietkun, Katarzyna; Giemza-Kucharska, Paulina; Zegarski, Tomasz; Nowacki, Maciej S.; Romańska-Gocka, Krystyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : During the process of skin ageing, changes occur in all skin layers and all cells, including the Langerhans cells. Aim: To assess whether any quantitative difference in the number of CD1a+ LC cells/mm 2 and HLA-DR+ LC cells/mm 2 as well as in their morphological features can be observed during the course of different types of skin ageing. Material and methods: The study was conducted in a group of 60 women, which was divided into three independent groups: group I with symptoms of menopausal skin ageing, group II with symptoms of photoageing, group III with symptoms of chronological ageing. Skin biopsy samples were taken from the pre-auricular region from all of the participants. The number of CD1a+ LC cells/mm 2 and HLA-DR+ LC cells/mm 2 as well as their morphological features were evaluated. Results : The frequency of CD1a+ LC and HLA-DR+ LC in all the studied groups was diverse. In groups I and III, the LC with large cell bodies and long, multi-branched processes were the majority. In group II, the LC had small cell bodies and their processes were mainly short and unbranched. Conclusions : The obtained results indicate the presence of quantitative and morphological changes of the CD1a+ LC and HLA-DR+ LC during the course of different types of skin ageing.